Pengaruh laju pemakanan proses milling terhadap perubahan temperatur pada pahat endmill karbida - Putra, H.S.; Rumbiak, A.S.; Lubis, S.Y.; Darmawan, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
Cutting Tool temperature has a significant role in the machining process in terms of tool life and workpiece properties. In dry machining process, cutting temperature condition must be monitored as excessive temperature rise can cause tool wear and damage to workpiece. Research on cutting heat has existed along with the development of metal cutting technology. Scientists have made many attempts to determine the cutting heat through theoretical analysis, numerical simulation, and experimental research. Measurement of cutting tool temperature requires a certain method because in milling process the cutting tool rotates to cut the workpiece. This research was condusted with an experimental research using an infrared thermal imager to obtain the result of carbide endmill toll in the face milling process of SKD61 (Special Kogyo Die)steel. The cutting parameters used were 1320 RPM spindle speed, 42, 98, 230 mm/min, and 0.5mm depth of cut. The milling process carried out with a time frequency of 5 minutes. The results of carbide endmill tool temperature measurement show that increasing the feed rate affects the temperature rise of the carbide endmill tool. At the feed rate of 42 mm/min, the highest temperature recorded was 152.3 ˚C, then at the feed rate of 98 mm/min, the highest temperature was 195 ˚C, and the feed rate of 230 mm/min had the highest temperature in this study, which was 219.4 ˚C.